2011
DOI: 10.1002/dys.433
|View full text |Cite
|
Sign up to set email alerts
|

Component Processes Subserving Rapid Automatized Naming in Dyslexic and Non‐dyslexic Readers

Abstract: The current study investigated which time components of rapid automatized naming (RAN) might predict group differences between dyslexic and nondyslexic readers (matched for age and reading level), and how these components relate to distinct reading measures. Subjects performed two RAN tasks (letters and objects) and data were analyzed through a response time analysis. Our results demonstrated that impaired RAN performance by dyslexic readers mainly stem from enhanced inter-item pause times and not from difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
1
33
0
3
Order By: Relevance
“…Araújo et al, 2011) documenting that the predictive role of RAN in reading performance is stronger in impaired readers than in typical readers. Such results not only underscore the importance of rapid naming skills for readers with reading disability (Araújo et al, 2011) but also support research indicating that RAN and phonological measures predict different aspects of reading (e.g. Savage & Frederickson, 2005; Wolf & Bowers, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Araújo et al, 2011) documenting that the predictive role of RAN in reading performance is stronger in impaired readers than in typical readers. Such results not only underscore the importance of rapid naming skills for readers with reading disability (Araújo et al, 2011) but also support research indicating that RAN and phonological measures predict different aspects of reading (e.g. Savage & Frederickson, 2005; Wolf & Bowers, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Araújo et al, 2011). It has been suggested that this poor performance among dyslexic readers is not due to less reading experience or limited letter names knowledge but to unsuccessful automatizing of rapid naming skills (e.g.…”
Section: Rapid Automatized Namingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the naming deficit persists into adulthood (e.g., Jones et al, 2009Jones et al, , 2016. Evidence show that dyslexic readers are maximally impaired in serial naming tasks -with matrix presentation of itemsthat require simultaneous activation/access of multiple visual and phonological representations that compete for output, as in the socalled rapid automatized naming tasks, RAN (Araújo et al, 2011b;Jones et al, 2010Jones et al, , 2008Wolf and Bowers, 1999;Wolf et al, 2002 However, individual stimulus presentation (i.e., discrete/confrontation naming tasks) also incurs a significant, albeit smaller, naming speed cost (e.g., Araújo et al, 2011a;Bowers and Swanson, 1991;Truman and Hennessey, 2006;see Jones et al (2009) for a direct contrast between discrete-and multiple-naming formats). Yet, it is still an open question which underlying processing stages are involved and contribute to impaired naming performance by dyslexic readers, which we investigate in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when total time to complete RAN tasks is experimentally segregated into a pause time— namely the duration of pauses between items in sequenced articulations—and articulation time —namely the time to articulate each item—pause time and not articulation time significantly predicts reading ability, in both normal and DD readers (Georgiou et al, 2006; Araújo et al, 2011b). Hence, these results point to the inter-item processing—namely the processes intercurring from attentional disengaging from one stimulus to name retrieval for the next one—as the locus that drives RAN-reading association.…”
Section: Introductionmentioning
confidence: 99%